1996
DOI: 10.2169/internalmedicine.35.39
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Lupus Erythematosus with Pulmonary Hypertension.

Abstract: A 50-year-old Japanese female with a long history of Raynaud's phenomenon presented with progressive dyspnea due to pulmonary hypertension. The diagnosis of systemic lupus erythematosus was confirmed by proteinuria, lymphocytopenia, bilateral pleurisy, and a seizure of convulsion which wasconsistent with neurological manifestations of systemic lupus erythematosus, whereas the antinuclear antibody showed a low titer. Despite improvement in the activity of systemic lupus erythematosus, steroid treatment did not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Abnormal vasospasm, Raynaud’s phenomenon, platelet abnormalities, vasculitis, thrombosis and thromboembolism have been suggested as possible pathogenetic factors [8, 24, 25]. Endothelial dysfunction is strongly implicated in the pathogenesis of autoimmune vasculitic diseases including lupus [26, 27].…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal vasospasm, Raynaud’s phenomenon, platelet abnormalities, vasculitis, thrombosis and thromboembolism have been suggested as possible pathogenetic factors [8, 24, 25]. Endothelial dysfunction is strongly implicated in the pathogenesis of autoimmune vasculitic diseases including lupus [26, 27].…”
Section: Discussionmentioning
confidence: 99%
“…Our recent systematic review of the literature [90] identified a number of clinical factors that may be associated with survival; magnitude of the elevation in P pa at diagnosis [78,89,91], thrombosis [89,92,93], thrombocytopenia [94], presence of an anti-cardiolipin antibody [89,92,93], concurrent pregnancy [95,96], infection [77], Raynaud's phenomenon [93,97], plexiform lesion [95] and pulmonary vasculitis [96]. Conversely, lupus central nervous system disease [89], lupus nephritis [89] and lupus disease activity [89,[98][99][100] have not been associated with survival in SLE-PH. It has been suggested that SLE-PAH patients have a better prognosis than SSc-PAH patients, where CONDLIFFE et al [44] reported a 3-yr survival rate of 75% in SLE-PAH compared to 47% in SSc-PA patients in the UK (p50.01).…”
Section: Sle-associated Phmentioning
confidence: 99%
“…Several small case reports/series have reported improvement with immunosuppressive therapy [87,[101][102][103]. However, others have reported clinical deterioration in SLE-PH despite immunosuppressive therapy [99,104]. Recent observational studies suggest that a subset of SLE-PH patients will improve with immunosuppression.…”
Section: Sle-associated Phmentioning
confidence: 99%
“…Lupus activity was not associated with SLE-PH survival in five case reports. [40][41][42][43][44] These patients had minimal or quiescent disease and normal complement or anti-double-stranded DNA (anti-dsDNA). In one retrospective cohort of mortality in SLE, 27 43 deaths occurred, and in six cases PH was the cause of death.…”
Section: Sle Disease Activitymentioning
confidence: 99%